2000
DOI: 10.1046/j.1365-2958.2000.02026.x
|View full text |Cite
|
Sign up to set email alerts
|

YscP, a Yersinia protein required for Yop secretion that is surface exposed, and released in low Ca2+

Abstract: The Yersinia Ysc apparatus is made of more than 20 proteins, 11 of which have homologues in many type III systems. Here, we characterize YscP from Yersinia enterocolitica. This 515‐residue protein has a high proline content, a large tandem repetition and a slow migration in SDS–PAGE. Unlike the products of neighbouring genes, it has a counterpart only in Pseudomonas aeruginosa and it varies even between Yersinia Ysc machineries. An yscPΔ97−465 mutant was unable to secrete any Yop, even under conditions overcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 55 publications
7
38
0
Order By: Relevance
“…Moreover, we could also confirm the findings of others that the yscP mutant secreted much lower levels of Yops than the wild-type strain (Fig. 1B) (35,46).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, we could also confirm the findings of others that the yscP mutant secreted much lower levels of Yops than the wild-type strain (Fig. 1B) (35,46).…”
Section: Resultssupporting
confidence: 90%
“…In this work, we have confirmed and extended previous findings regarding the role of YscP in the TTSS by Yersinia (35,46) and shown that yscP-null mutants were severely affected in their ability to secrete Yop effector proteins. In contrast, the YscF protein was secreted in elevated amounts.…”
Section: Discussionsupporting
confidence: 90%
“…The latter two proteins are slightly larger (FliK, 42 kDa; YscP, 50 kDa) than Spa32 (32 kDa), and indeed, there are many gaps between the homologous amino acid regions of FliK (as well as YscP) and Spa32. However, the placements of spa32, invJ, fliK, and yscP in the respective operons were all similar, and each of the gene products was secreted (6,32,36,40,42; this study). Furthermore, the production of each protein was required for a functional type III secretion system (Spa32, InvJ, and YscP) (7, 36, 42; this study) or flagellar export system (FliK) (20,33,48).…”
Section: Resultsmentioning
confidence: 51%
“…Deletion mutants showed that abolishing the complete gene leads to a loss of secretion of Yops, and a functional protein is necessary for the delivery of the effectors into target cells (Stainier, et al, 2000). It was noted as well that it shows more variability than any other protein in the T3SS between Y. pseudotuberculosis, Y. pestis, and Y. enterocolitica (Stainier, et al, 2000). YscP from Y. enterocolitica has additional 60 amino acids that appear to be part of a repeat compared to Y. pseudotuberculosis and Y. pestis.…”
Section: Yscpmentioning
confidence: 99%